Vertical Profile of Zooplankton in Lubuk Siam Lake Siak Hulu Sub District, Kampar District - Intan S, Yeni Debora; Siagian, Madju; Dahril, Tengku (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2018)
AbstractLubuk Siam lake is an oxbow lake that is located in the Siak Hulu sub-district, Kampar district. There were several human activities around the Lubuk Siam Lake such as agriculture and palm plantation. This study aims to understand zooplankton vertical distribution in that lake and it was conducted in February to March 2017. There were 3 stations, namely Station 1 (inlet area), Station 2 (fish cage area), and Station 3 (outlet area). In each station, there were 3 sampling points: at the surface, 2 secchi depth (126 cm) and 3 secchi depth (189 cm). Water samples were taken once/week for 3 weeks periode. Water quality parameters measured were: temperature, transparency, pH, nitrate, dissolved oxygen and free CO2 . Result shown that total abundance of zooplankton in station I: 945-1680 ind/L, Station II: 1365-2190 ind/L, and Station III: 1.230-2.085 ind/L. Water quality parameters measured were as follow : transparency 63 - 69 cm, temperature 27.5 – 31.10C, pH 6.83 – 7.27, dissolved oxygen 4.0984 – 7.8399 mg/L, free CO2 5.296 – 15.981 mg/L, and nitrate 0.0694 – 0.1688 mg/L.Keywords: Lake, Lubuk Siam, Zooplankton